Possessions : the history and uses of haunting in the Hudson Valley - Richardson, Judith (Harvard University Press, 2003)
"The cultural landscape of the Hudson River Valley is crowded with ghosts-- the ghosts of Native Americans and Dutch colonists, of Revolutionary War soldiers and spies, of presidents, slaves, priests, and laborers. Possessions asks why this region just outside New York City became the locus for so many ghostly tales, and shows how these hauntings came to operate as a peculiar type of social memory whereby things lost, forgotten, or marginalized returned to claim possession of imaginations and territories."--Dust jacket flap